Adaptive Network Design for Multiple Gliders Observation of Mesoscale Eddy - Gao, Zhanwen; Chen, Ge; Song, Yang; Zheng, Jie; Ma, Chunyong (Frontiers in Marine Science, 2022)
With its excellent endurance, good maneuverability and track controllability, glider has become one of the important equipment to obtain ocean field data. The network observation of multiple gliders will be the main approach of ocean observation in the future. However, how to plan the glider path in a reasonable way and how to design the optimal observation network consisting of multiple gliders in an eddy have not been well solved. As an effort to tackle this problem, an adaptive network design algorithm for multiple gliders in mesoscale eddies observation which referred as “Optimal Sampling” is proposed in this paper. Simulation experiments of tracking a target eddy in the South China Sea (SCS) show that the proposed algorithm cannot only realize the adaptive network design for multiple gliders, but also ensure the uniform sampling inside the eddy. Compared with the traditional method which samples eddy along a fixed path, the observation data obtained by the solution proposed in this paper are more valuable to describe the essential temperature characteristics of eddies. The residual errors computed from the interpolation of the sampled field is also smaller.